Factors that contribute to turnover intention among non-executive level employees at Malaysia Airport Niaga, Sepang / Amira Nur Md Isa - Md Isa, Amira Nur (Faculty of Business and Management, 2010)
Employees are the most valuable asset in any organization. Organizations invest a lot on their employees in terms of induction and training, developing, maintaining and retaining them in their organization. Therefore, managers at all costs must minimize employee’s turnover. This research examines the relationship between three factors of turnover intention which are task orientation, generation differentials and psychological contract among non-executive level employees at Malaysia Airport Niaga Sdn Bhd, Sepang. In addition, the study also attempts to determine the differences in the turnover intention based on demographic variables (age and tenure). The study also hypothesized that there are significant differences in the turnover intention of employees at Malaysia Airport Niaga Sdn Bhd, Sepang at different age and length of service; and there is a dominant factor influencing turnover intention among employees in the organization. Three research instruments were used to obtain data: a questionnaire, interview and observation. A total of 50 respondents were randomly selected as the sample of study and data was analyzed by “Statistical Package for Social Science” (SPSS Window) Version 17.0. Task orientation and generation differentials demonstrate the strongest relationship. These findings show that the related factors should have given attention to retain employees in the organization. Some suggestions have been recommended for the organization to be more efficient. Thus, this research will contribute significantly to organizations wanting to encourage workers to be committed and continue their service with them in this organization.